Strategi Bauran Pemasaran Dalam Meningkatkan Omzet Penjualan pada Cafe Jolly Coffee Surabaya - Sari, Dwi Retno Anom; Prabowo, Budi (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The research conducted took the object of research at Cafe Jolly Coffee Surabaya. Being one of the cafes in Surabaya City which has a strategic location in the middle of many existing cafes. The purpose of the research conducted was to find out and analyze how the marketing mix strategy carried out by Cafe Jolly Coffee Surabaya to increase sales turnover. Using descriptive qualitative research methods using SWOT analysis as the research method. Researchers collect data through interviews, observations, and documentation related to the 7P marketing mix which includes product, price, promotion, place, people, process, physical appearance. Jolly Coffee Surabaya has a score of internal factors, namely strengths of 3.02 and weaknesses having a score of 0.34, while from external factors it has an opportunity score of 2.48 and a threat score of 0.62 through IFAS and EFAS analysis. Next, Jolly Coffee Surabaya is in Quadrant I (one) which supports an aggressive strategy to take advantage of existing opportunities by using its strengths. For the IE matrix, the results show that the business company is in Quadrant I (one) position, namely Growth Oriented Strategy in order to increase sales turnover at Cafe Jolly Coffee Surabaya. Keywords: 7P Marketing mix, SWOT Analysis, Sales Turnover